Volume 13: Transportation Systems 2013
DOI: 10.1115/imece2013-65703
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Aerodynamic Drag on Vacuum Tube High Speed Train

Abstract: This work involves numerical simulations based on finite volume method to study the effects of different factors on the aerodynamic drag on a vacuum tube train running at subsonic and transonic speeds in a partially vacuum tunnel. Investigation includes the study of the effects of the shapes of head, tail, vacuum pressure and also blockage ratio of the tunnel on aerodynamic drag on a high speed train. The simulation is performed by using fluent software. Two dimensional, axisymmetric, compressible Navier-Stoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Different shapes of the pod have been studied in previous studies to reduce the aerodynamic drag on the pod. 10,[27][28][29] This study used the ideal pod shape for both pods. For this purpose, both pods' semicircular nose and tail were selected to study the aerodynamic characteristics.…”
Section: Computational Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Different shapes of the pod have been studied in previous studies to reduce the aerodynamic drag on the pod. 10,[27][28][29] This study used the ideal pod shape for both pods. For this purpose, both pods' semicircular nose and tail were selected to study the aerodynamic characteristics.…”
Section: Computational Domainmentioning
confidence: 99%
“…The researchers' primary objective for the Hyperloop system is to reduce the aerodynamic drag value, which will result in economic efficiency and feasibility of high-speed trains/pods. Various researchers study the aerodynamic properties of the Hyperloop system by changing the speed of the pod, 7,[9][10][11][12][13] the pressure inside the tube, 7,[9][10][11]13 the shape of the pod, 9,14 the variation of the blockage ratio (i.e., which is the ratio of the cross-sectional area of the pod to the crosssectional area of the tube), [10][11][12] and the length of the tube. 7 Increasing the pod's speed or pressure of the tube or blockage ratio (BR) or size of the pod results in an increase in the value of aerodynamic drag value and vice versa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different geometries of trains have been identified and modelled. Bibin et al (2013) found that a blockage ratio of 0.25 would be most appropriate for vacuum tube transportation. This effect taking into consideration with the assumption that the flow is steady three dimensional, compressible.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, aerodynamics of the HTS Maglev-ETT system is a new subject needed further research. Many groups have simulated aerodynamics of the vacuum tube train and analyzed the effect of the vehicle speed, blockage ratio, and air pressures [9,10] . Nonetheless, due to the lack of experimental facilities, there is little work on the related experiments.…”
Section: Introductionmentioning
confidence: 99%